Electronic circuits - fundamentals & applications - Tooley, Mike. ([S.l.] : Routledge, 2006)
Electronic Circuits is a unique combination of a comprehensive reference text and a practical electronics handbook in one volume. Mike Tooley provides all the essential information required to get to grips with the fundamentals of electronics, detailing the underpinning knowledge necessary to appreciate the operation of a wide range of electronic circuits, including amplifiers, logic circuits, power supplies and oscillators. The third edition now offers an even more extensive range of topics, with extended coverage of practical areas such as circuit construction and fault finding, and new topics including circuit simulation, electronic CAD and a brand new chapter devoted to the PIC microcontroller. A new companion website at http://www.key2electronics.com offers the reader a set of spreadsheet design tools that can be used to simplify circuit calculations, as well as circuit models and templates that will enable virtual simulation of circuits in the book. These are accompanied by on-line self-test MCQs per chapter with automatic marking, to enable students to continually monitor their own progress and understanding. A bank of on-line questions for lecturers to set as assignments is also available on http://textbooks.elsevier.com The book$1 (Bs content is matched to the latest pre-degree level courses (from Level 2 up to, and including, Foundation Degree and HND), making this an invaluable reference text for all study levels, and its broad coverage is combined with practical case studies, based in real-world engineering contexts throughout the text. The unique combination of a comprehensive reference text, incorporating a primary focus on practical application, ensures this text will prove a vital guide for students and also for industry-based engineers, who are either new to the field of electronics, or who wish to refresh their knowledge. Yet unlike general electronics reference texts available, Electronic Circuits offers this essential information at an affordable prices